Endogenous cell wall degrading enzyme LytD is important for the biocontrol activity of Bacillus subtilis - Wang, Luotao; Huang, Jianquan; Chen, Si; Su, Xin; Zhang, Xun; Wang, Lujun; Zhang, Wei; Wang, Zhenshuo; Zeng, Qingchao; Wang, Qi; Li, Yan (Frontiers in Plant Science, 2024)
Autolysins are endogenous Cell Wall Degrading Enzyme (CWDE) in bacteria to remodel the peptidoglycan layer of its own cell wall. In Bacillus subtilis genome, at least 35 autolysin genes have been identified. However, the study of their roles in bacterial physiology has been hampered by their complexity and functional redundancy. B. subtilis GLB191 is an effective biocontrol strain against grape downy mildew disease, the biocontrol effect of which results from both direct effect against the pathogen and stimulation of the plant defense. In this study, we show that the autolysin Nacetylglucosaminidase LytD, a major autolysin of vegetative growth in B. subtilis, plays an important role in its biocontrol activity against grape downy mildew. Disruption of lytD resulted in reduced suppression of the pathogen Plasmopara viticola and stimulation of the plant defense. LytD is also shown to affect the biofilm formation and colonization of B. subtilis on grape leaves. This is the first report that demonstrates the role of an endogenous CWDE in suppressing plant disease infection of a biological control microorganism. These findings not only expand our knowledge on the biological function of autolysins, but also provide a new target to promote the biocontrol activity of B. subtilis.